MONTESSORI MATHEMATICS FOR STUDENTS WITH PERVASIVE DEVELOPMENTAL DISORDER - NOT OTHERWISE SPECIFIED - Dyah Ayu Sulistyaning Cipta; Era Dewi Kartika; Anik Kurniawati (Prima: Jurnal Pendidikan Matematika, 2022)
Montessori is a learning method that uses the surrounding environment as a learning resource. This research is aimed at describing how the Montessori method is applied to Mathematics for students who survive Pervasive Developmental Disorder - Not Otherwise Specified (PDD-NOS). The research method used is descriptive qualitative. The research subjects were PDD-NOS grade V SD students in inclusive schools. The research instruments were documentation, observation, and interviews. The results showed that students with PDD-NOS who have delays in communication can more easily accept mathematics learning using the Montessori method. This is supported by the Montessori concept which allows PDD-NOS students to use lego in learning fractions.